Bridging the Knowledge Gap with Multimodal Teaching for Stroke Caregivers - Mondal , Jharna; Mandal, Debarchana; Bera, Saraswati; Dolai, Bidhan (The Ukrainian Scientific Medical Youth Journal, 2025)
stroke significantly impacts mortality and morbidity worldwide, especially in low- and middle-income countries like India, imposing considerable challenges on caregivers who often lack adequate education and resources for post-stroke care. This study investigates the effectiveness of a multimodal teaching intervention tailored for caregivers of stroke survivors. Utilizing a quasi-experimental design, 62 caregivers were assigned to experimental and control groups, with pre- and post-test knowledge assessments conducted using structured questionnaires. Results indicate a substantial increase in the experimental group’s knowledge scores, rising from a mean of 7.13 to 13.61 (p < 0.05), while the control group showed minimal improvement. Remarkably, communication skills and understanding of the concept of stroke yielded the highest gains. These findings affirm that multimodal teaching effectively enhances caregivers’ knowledge, suggesting that such innovative educational strategies should be integrated into caregiver education programs to improve outcomes for both caregivers and stroke patients. Limitations include small sample size, regional focus, and potential bias in self-reported assessments.